Does global longitudinal strain improve stratification risk in heart failure with preserved ejection fraction? - Haddad, Assia; Guerchani, Mohamed Karim; Bessi, Nadia Ould; Djermane, Dalila; Mokhtar, Omar Ait; Himeur, Hakim; Benkhedda, Salim (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: Heart Failure with Preserved Ejection Fraction (HFPEF) accounts for more than half of the cases of heart failure. Long regarded as an abnormality of left ventricular diastolic function, recent studies using longitudinal strain (two-dimensional speckle tracking mode) have suggested that left ventricular longitudinal systolic function is altered in HFPEF. Despite these interesting pathophysiological perspectives, the data in the literature on the prognostic value of the alteration of longitudinal strain are controversial. Given these conflicting results, it is difficult to confirm the magnitude and prevalence of impaired LV longitudinal systolic function in patients with HFPEF and its prognostic relevance. Purposes: This work aims to study the prognostic value of Global the left ventricle’s Global Longitudinal Strain (GLS) Algerian cohort of patients with HFPEF. Patients and methods: We conducted a monocentric prospective observational study from April 2018 to April 2020, with a minimum follow-up of 1 year for each recruited patient. We included patients over the age of 18 referred to the echocardiography laboratory for chronic or acute HFpEF, defined according to the criteria of ESC 2016. 153 consecutive patients underwent clinical examination, biological tests, and echocardiography with measurement of GLS at rest, in addition to routine management by the attending physicians. Results: 153 patients were collected. The average age of our patients is 73 +/- 11 years ranging from 42 to 91 years old. The female population is predominant with a rate of 67%. Comorbidities are predominant mainly by arterial hypertension (86%) and diabetes (64%), with a history of atrial fibrillation (46%). 63% of patients have impaired GLS (< 16%). Contrary to our hypothesis, GLS was not shown to be a powerful predictor of cardiovascular events in HFPEF patients either in dichotomous analysis (OR = 0.79; p = 0.64) or in continuous analysis (OR = 0.97; p = 0.69).We were able to identify that congestive venous signs, anemia, and pulmonary hypertension, are the main independent prognostic factors in our Algerian population study. Conclusion: We were unable to demonstrate the prognostic role of mpaired GLS in our population of patients with HFPEF.